2020
DOI: 10.1177/0361684320918243
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Girls Who Engage in Serious Delinquency and Their Young Adult Outcomes

Abstract: Girls are increasingly becoming involved with the juvenile justice system; however, what brings girls to engage in delinquency or what obstacles these girls face later in life resulting from adolescent criminal behavior is understudied. In the present study, we used latent class analysis to identify subtypes of risks among adolescent girls ( N = 1,174) who have engaged in delinquent behaviors and mixture modeling to determine what distal psychological, social, educational, and economic outcomes in young adulth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Girls are statistically more inclined toward non-aggressive delinquent behaviours, such as minor property crimes or substance use, while boys are more inclined toward violent and aggressive delinquent acts (Liu & Miller, 2020). Smith et al (2020) examined the varying degrees of girls' involvement in delinquency, identifying four distinct subtypes distinguished by the severity of their self-reported victimisation experiences and mental health issues. They found that girls with higher levels of victimisation tended to report increased engagement in delinquent acts.…”
Section: Gender and Juvenile Delinquency And Victimisationmentioning
confidence: 99%
“…Girls are statistically more inclined toward non-aggressive delinquent behaviours, such as minor property crimes or substance use, while boys are more inclined toward violent and aggressive delinquent acts (Liu & Miller, 2020). Smith et al (2020) examined the varying degrees of girls' involvement in delinquency, identifying four distinct subtypes distinguished by the severity of their self-reported victimisation experiences and mental health issues. They found that girls with higher levels of victimisation tended to report increased engagement in delinquent acts.…”
Section: Gender and Juvenile Delinquency And Victimisationmentioning
confidence: 99%
“…Roe-Sepowitz and Hickle (2011) noted that girl arsonists more often reported a history of childhood abuse, higher scores on a suicide ideation scale and that they were more likely to set fire at school due to other abuses like drug abuse which is less in our study population. Smith et al (2020), on a review of literature, established that girls are increasingly becoming involved with the juvenile justice system because of the crimes they commit. The girl's involvement in criminality came out clearly from the findings represented in 2020) which also added smoking as an act of children's offenses.…”
Section: Delinquent Behaviors Ofmentioning
confidence: 99%
“…According to a study by Smith et al (2020), juvenile justice involvement among girls is rising due to the crimes they commit. The data presented in table 3 showed that as sexual abuse increases, juvenile delinquency also increases positively.…”
Section: Correlation Coefficient Between Sexual Abuse and Juvenile De...mentioning
confidence: 99%